Optimal reliability of systems subject to imperfect fault-coverage - Amari, S.V.; Dugan, J.B.; Misra, R.B. (IEEE transactions on reliability, 1999)
This paper maximizes the reliability of systems subjected to imperfect fault-coverage. The results include the effect of common-cause failures and 'maximum allowable spare limit'. The generalized results are presented and then the policies for some specific systems are given. The systems considered include parallel, parallel-series, series parallel, k-out-of-n, and NMR (k-out-of-(2k-1)) systems. The results are generalized for the non s-identical component case.